2019
DOI: 10.1111/1462-2920.14715
|View full text |Cite
|
Sign up to set email alerts
|

Species interactions and distinct microbial communities in high Arctic permafrost affected cryosols are associated with the CH4 and CO2 gas fluxes

Abstract: Summary Microbial metabolism of the thawing organic carbon stores in permafrost results in a positive feedback loop of greenhouse gas emissions. CO2 and CH4 fluxes and the associated microbial communities in Arctic cryosols are important in predicting future warming potential of the Arctic. We demonstrate that topography had an impact on CH4 and CO2 flux at a high Arctic ice‐wedge polygon terrain site, with higher CO2 emissions and lower CH4 uptake at troughs compared to polygon interior soils. The pmoA sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 97 publications
4
25
0
Order By: Relevance
“…According to the whole genome sequences, type strains of P. silesiensis A3 T , P. umsongensis DSM16611 T and P. laurylsulfatiphila AP3_16 T , as well as P. arsenicoxydans strains ACM1 and E3, do not contain in their genome naphthalene 1,2-dioxygenase-related genes (Kaminski et al 2018;Furmanczyk et al 2018;Kwon et al 2003;Altshuler et al 2019). This observation further indicated that isolates obtained in this study, affiliating with the abovementioned bacterial species, acquired the naphthalene biodegradation capability through HGT.…”
Section: Discussionsupporting
confidence: 52%
“…According to the whole genome sequences, type strains of P. silesiensis A3 T , P. umsongensis DSM16611 T and P. laurylsulfatiphila AP3_16 T , as well as P. arsenicoxydans strains ACM1 and E3, do not contain in their genome naphthalene 1,2-dioxygenase-related genes (Kaminski et al 2018;Furmanczyk et al 2018;Kwon et al 2003;Altshuler et al 2019). This observation further indicated that isolates obtained in this study, affiliating with the abovementioned bacterial species, acquired the naphthalene biodegradation capability through HGT.…”
Section: Discussionsupporting
confidence: 52%
“…Only SO 2 has significant correlations with all other pollutants, because it is mainly from fuel combustion and can attach to PM 2.5 and PM 10 [22]. The global air quality experienced a dramatic improvement throughout the pandemic of COVID-19 [34,46] because the lockdown supplied a relatively non-industrial period [34][35][36][37][38][39][40][41][42][43]46,47,49,50]. Isolation is an effective way to block the spread of COVID-19 [34][35][36][37][38][39][40][41][42][43][44][45][46][47]; however, this means that people have to be restricted to their homes or somewhere else.…”
Section: Availability Of Lockdown Policy's Response To the Diffusion Of Covid-19mentioning
confidence: 99%
“…E. americana RIT713 [75]. In addition, strain E4 [76], isolated from permafrost soil, was included to ascertain its name and taxonomic position. There is no report of the pathogenicity test for the five other strains.…”
Section: Bacterial Strains and Characterizationmentioning
confidence: 99%
“…The genome of E. americana B6-1 was deposited in the GenBank database under the accession CP048243 in the Genome and SAMN13930952 in the BioSample. In addition, four other E. americana genomes (including E. americana ATCC 33852 [72], E. americana CCUG 14506T [73], E. americana NCTC12157 [74], and E. americana RIT713 [75]), and a wrongly named species E4 [76] (Supplementary Table S3) were downloaded from the National Centre for Biotechnology Information (NCBI) (https://www.ncbi.nlm.nih.gov/) genome repository and reannotated following the same pipeline as B6-1. The quality of all the genome assembly was assessed using Quast (v5.0.2) [85].…”
Section: Dna Extraction Genome Sequencing and Annotationmentioning
confidence: 99%